Vowel Duration in the Spanish of the Great Metropolitan Area of Costa Rica - Stensrud Krohn, Haakon (2019)
This paper describes an acoustic analysis of the vowel duration in Spanish words read by Spanish speaking university students from the Great Metropolitan Area of Costa Rica. The results reveal three factors in the linguistic context that increase the vowel duration in disyllabic words. Firstly, vowels in the first syllable are longer when stressed than when unstressed. Moreover, vowels in the first syllable are longer when the syllable is open than when it is closed. Finally, stressed vowels in closed syllables are longer when they are in the second syllable of the word than in the first one.